Autonomous motivation, cardiorespiratory fitness, and exercise in rheumatoid arthritis: Randomised controlled trial. (July 2021) - Veldhuijzen van Zanten, Jet J.C.S.; Fenton, Sally A.M.; Rouse, Peter C.; Ntoumanis, Nikos; Osailan, Ahmad; Yu, Chen-an; Metsios, George S.; Kitas, George D.; Duda, Joan L.
Abstract: Objective: Rheumatoid arthritis (RA) is an autoimmune disease, characterised by high-grade systemic inflammation, pain, and swollen joints. RA patients have an increased risk for cardiovascular disease (CVD). This study examined if a 3-month individualised RA-tailored exercise programme with one-on-one Self-Determination Theory (SDT)-based support for physical activity (PA) facilitated autonomous motivation, increased PA behaviour, and induced greater improvements in cardiovascular and RA-related disease characteristics, and wellbeing in RA, compared to a standard provision tailored exercise programme. Methods: 115 RA patients were randomised into either the SDT-based psychological intervention + exercise programme (experimental group) or an exercise programme only (control group). Cardiorespiratory fitness (primary outcome), self-reported PA, disease characteristics, CVD risk, wellbeing, and SDT constructs were assessed at baseline (pre-intervention), 3 months (post-intervention), 6 months, and 12 months follow-up. Mixed linear modeling was used to examine within- and between participant changes in these outcome measures. Results: In 88 patients with complete baseline data, cardiorespiratory fitness did not change from baseline to 3-, 6- or 12 months in either group. CVD risk, disease characteristics, wellbeing, and need satisfaction did not change, with the exception of diastolic blood pressure. Significant group by time interaction effects were found for functional ability (6- & 12-months), CVD risk (6-months) and PA (3-months). Autonomous motivation increased and controlled motivation decreased more in the experimental group compared to the control group at 3 months. Conclusions: Despite improving quality of motivation for exercise, no changes in cardiorespiratory fitness or other psychological and physiological health outcomes were found. This suggests more intensive support is needed when initiating an exercise programme to achieve health benefits in RA. Highlights: A self-determination theory-based exercise programme can successfully improve quality of motivation in RA. Despite changes in motivation, no changes were seen in cardiovascular disease risk or wellbeing. Intense supervision is needed to facilitate exercise at levels sufficient for health benefits in RA.